Synthesis of Novel Danshensu Alkamine Derivatives as Potential Anti-Myocardial Ischemia Agents - Shu1, Jing-Jing; Zhang2, Chuan; Wang2, Ting-Fang; Zou2, Hao; Jin2, Lei; Gu1, Wei-Ying; Zhang1, Li-Chao (Asian Journal of Chemistry, 2014)
Ten novel danshensu alkamine derivatives were synthesized and the preliminary biological activity of these complexes were investigated. The bioassay results indicated that some of derivatives exhibit significant activities on protecting hypoxic H9C2 cardiomyocytes.